Investigation of Coffee Export Dynamics in Indonesia - Sofyan, Muhammad Idham; Sebayang, Toto Edrinal; Syafni, Viani Khairunnisa (BISMA (Bisnis dan Manajemen), 2018)
The aim of this research is to discover the factors that influence the export volume of Indonesian coffee, the response of Indonesian coffee exports to shock variables that affect it, and the contribution of the variables affecting the coffee export to the change of export variables in Indonesia. The study used only secondary data (time series) and the data was collected from The Central Bank of Indonesia (BI), Central Bureau of Statistics (BPS) and International Coffee Organization (ICO). This study takes a monthly period starting from 2010: M01 to 2015: M12 by using the Vector Error Correction Model (VECM) analysis. The result of this research indicates that the data at the first difference is stationer and that there exist cointegration among the variables. While the Granger Causality test shows that there is a two-way relationship between domestic coffee prices and international coffee prices and the occurrence of a direct relationship between the domestic coffee price to the export volume of Indonesian coffee. The Impulse Response Function states that the shock of each variable will produce a sharp shock at the beginning of the period but will reach a stable point at the end of the period. The result of Factor Error Variance Decomposition analysis shows that the shock variables that affect it are still dominated by the variable itself